Advantage of Ti-Doped Ge2Sb2Te5 Material for Phase Change Memory Applications. (20th October 2015) - Cao, Liangliang; Ji, Xinglong; Zhu, Wenqing; She, Qiumin; Chen, Yan; Hu, Zhigao; Guo, Shuang; Song, Zhitang; Rao, Feng; Qian, Bo; Wu, Liangcai
Abstract : Ti-doped Ge2 Sb2 Te5 (GSTT) materials have been investigated for phase change memory (PCM) applications. Compared with GST, GSTT5.67% phase change material has a higher crystallization temperature (∼230°C), a higher crystallization activation energy (2.79 eV) and a better data retention ability (∼134°C for 10-year). The PCM cell based on GSTT5.67% exhibits lower power consumption than GST based one. Endurance up to 1 × 10 4 cycles with high/low resistance ratio of over one order of magnitude has been achieved.